Impact of SO(2) on Arabidopsis thaliana transcriptome in wildtype and sulfite oxidase knockout plants analyzed by RNA deep sequencing - Hamisch, Domenica (The New phytologist, 2012)
© 2012 The Authors. New Phytologist © 2012 New Phytologist Trust.